Upwelling phenomenon in the marine regions of Southern Central of Vietnam: a review - Bui, Hong Long; Phan, Minh Thu (Vietnam Journal of Marine Science and Technology, 2022)
Upwelling is an oceanographic phenomenon that involves the physical process and contributes to changes in chemistry, biology, and natural resources. So, systematically, it is the particular ecosystems of whole marine regions with the upwelling. The strong upwelling waters in South Central Regions of Vietnam have uncertain features of the East Vietnam Sea (Bien Dong) and special characteristics of a coastal upwelling area, recorded in international scientific papers in the twentieth century. Their first signals were discovered in the early 1930s through conceptual ideas. The upwelling phenomenon is officially confirmed by scientific results of marine investigations of the NAGA Expedition (1959–1961). The paper aims to review and discuss the physical from Vietnamese investigation and results since 1990s. The following factors are the most contributing to forming and developing the strong upwelling in Southern Central Waters: (1) Influence scale (Mezo- and micro-scale); (2) Forming causes and developing mechanism of upwelling phenomenon, such as monsoon, morphography, shoreline, and western boundary current system of the East Vietnam Sea; (3) Influence of the water-mass from Mekong River on the upwelling area; (4) Ecological environmental consequences; (5) Impacts of the atmospheric-oceanic interaction processes on the western EVS on upwelling. Additionally, the review has targeted findings of upwelling phenomenon mainly in Vietnamese waters based on remote sensing analysis and reanalysis data series to simulate their forming, mechanizing, fluctuating models and the impacts of upwelling in the EVS on resources and ecosystems. The coupled atmosphere-ocean models resulted the upwelling mechanisms and formation. The long-time series of upwelling phenomenon (Macroscale) were evaluated by remote sensing and reanalyzed data series. It is also providing the supplementing and detailing causes and mechanisms of upwelling formation; impacts and interactions of upwelling on marine physics and hydrodynamics (ocean vortexes, seawater temperature), biochemical (nutrients, plankton organisms), and resources (fish, seafood). Within the framework of strong upwelling waters in the Southern Central Regions (Vietnam), the review has not only mentioned partly clarified scientific results but also indicates the limitations and challenges which were faced and encountered in the forecasters of upwelling phenomena in the future.